Reinterpretasi Aborsi: Studi Tafsir Feminis atas Hak Kesehatan Reproduksi Perempuan - Apriani, Laelati Dwina; Muhamad Iqbal Mustofa; Eni Zulaiha (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The issue of abortion in Islam has been a long-standing debate among scholars, particularly concerning women's reproductive rights. In many classical interpretations, abortion is often regarded as a prohibited act of murder, based on Qur'anic verses such as QS. Al-An’am [6]: 151 and QS. Al-Isra [17]: 31. These interpretations frequently overlook the context of women as legal subjects with specific needs and conditions, such as trauma from sexual violence or threats to their life. This article explores the reinterpretation of abortion in Islam through the lens of feminist exegesis, emphasizing pragmatic approaches and the principles of maqashid syariah. Feminist exegesis offers a perspective that recognizes women's reproductive rights as integral to the protection of life (hifzh an-nafs) and lineage (hifzh an-nasl). Through an analysis of feminist scholars like Faqihuddin Abdul Qodir and Husein Muhammad, this article demonstrates that abortion can be permissible under certain circumstances for the welfare of women. The findings indicate that this reinterpretation not only provides practical solutions but also aligns with the primary objectives of Islamic law, namely ensuring justice and safeguarding women's rights within a humanistic religious framework.